Integrating women’s empowerment and nutrition in national agricultural surveys: Country experiences, perspectives, and the path forward - Quisumbing, Agnes R.; Go, Ara; Malapit, Hazel J.; Heckert, Jessica; Osei, Kwame A.; Di Giuseppe, Stefania; Kamara, Momoh B.; Brunelli, Chiara (International Food Policy Research Institute, 2025)
This workshop was facilitated by Maria G. Nassuna-Musoke and Nicoletta Buono. The named presentations are: